2007
DOI: 10.1111/j.1365-2699.2007.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Uniform phenotype conceals double colonization by reed‐warblers of a remote Pacific archipelago

Abstract: Aim  Remote oceanic islands often provide good illustrations of adaptive radiations, but phylogenetic studies have also demonstrated unexpected multiple colonization events for a given archipelago. In this study we investigate the relationships among endemic populations of the Marquesas reed‐warbler, Acrocephalus mendanae Tristram, 1883, which have colonized nearly all islands of this remote Polynesian archipelago, and which exhibit a very uniform plumage pattern. We study the phylogeny and morphology of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 83 publications
(77 reference statements)
0
45
0
Order By: Relevance
“…Thibault, 1984;Dickinson, 2003), whereas some authors suggested splitting this species into three, mainly because of wide geographical separation: A. caffer s.s. on the Society Islands, A. atyphus on Tuamotu, and A. mendanae in the Marquesas (Pratt et al, 1987;BirdLife International, 2000;Cibois et al, 2011a, b). Using mitochondrial sequence data, Cibois et al (2007) showed that A. mendanae formed two independent lineages, which they proposed be treated as specifically distinct: A. percernis (closely related to A. atyphus) and A. mendanae s.s. (sister to A. aequinoctialis). In a later study, Cibois et al (2008) analyzed mitochondrial DNA from extinct Acrocephalus taxa from different Society Islands, and concluded that A. caffer s.l.…”
Section: Acrocephalidaementioning
confidence: 99%
“…Thibault, 1984;Dickinson, 2003), whereas some authors suggested splitting this species into three, mainly because of wide geographical separation: A. caffer s.s. on the Society Islands, A. atyphus on Tuamotu, and A. mendanae in the Marquesas (Pratt et al, 1987;BirdLife International, 2000;Cibois et al, 2011a, b). Using mitochondrial sequence data, Cibois et al (2007) showed that A. mendanae formed two independent lineages, which they proposed be treated as specifically distinct: A. percernis (closely related to A. atyphus) and A. mendanae s.s. (sister to A. aequinoctialis). In a later study, Cibois et al (2008) analyzed mitochondrial DNA from extinct Acrocephalus taxa from different Society Islands, and concluded that A. caffer s.l.…”
Section: Acrocephalidaementioning
confidence: 99%
“…For example, reed warblers have colonized nearly all the islands of the Marquesas and look remarkably similar across the islands. However, molecular data indicate that the Marquesas reed warbler includes two independent lineages: the northern Marquesas reed warbler, closely related to the Tuamotu reed warbler, and the southern Marquesas reed warbler, sister to that of Kiribati (Cibois et al 2007). Both colonizations occurred ca 0.6 Ma, more recently than the formation of the islands, and suggest that the bird is a 'supertramp', colonizing remote islands easily and repeatedly.…”
Section: Affinities Within the Central Pacificmentioning
confidence: 99%
“…AMNH 195478, 195479, 195486, 195491, and 195494 are not now in AMNH and may have been exchanged with other institutions, although the catalog was not so marked. Recent mtDNA studies by Cibois et al (2007) indicated that Acrocephalus populations in the Marquesas are polyphyletic. Their proposed classification included populations from the southern Marquesas in the species A. mendanae; Cibois et al (2008) extended their study to include Acrocephalus populations in the Society Islands.…”
Section: Conopoderas Caffra Consobrina Murphy and Mathewsmentioning
confidence: 99%
“…Dickinson (2003: 585) listed aquilonis as a subspecies of A. caffer and referenced other treatments. Recent mtDNA studies by Cibois et al (2007) showed that populations from the northern Marquesas comprised an independent lineage; their proposed classification included aquilonis from Eiao in the species A. percernis.…”
Section: Conopoderas Caffra Aquilonis Murphy and Mathewsmentioning
confidence: 99%
See 1 more Smart Citation